Pengaruh Pemberian Kompres Lidah Buaya (Aloe Vera) terhadap Penurunan Suhu Bayi Pasca Imunisasi DPT-HB - Novidha, Donna Harriya; Zubaidah, Zubaidah (Universitas Faletehan, 2023)
DPT-HB (diphtheria, pertussis, tetanus, hepatitis B) immunizations can cause local reactions such as pain, redness, and swelling. Generally, children are a little fussy and feverish after immunization. Aloe vera therapy was chosen because 95% of the content is water which can reduce fever through a mechanism of absorbing body heat. The purpose of this study was to determine the effects of aloe vera poultice to lower the body temperature of babies after DPT-HB immunization in the Work Area of Pasar Baru Health Center, Merangin District. The study design was pre-experimental with a one group pretest-posttest design. The sample of this study consisted of 20 babies who were selected by accidental sampling method. The primary data collection involved measuring the babies' body temperatures with a thermometer, administering aloe vera therapy wrapped in a sterile gauze, and using an observational sheet to record the results of the temperature measurements. A t-test was used for data analysis. The results of the study showed that the mean of babies’ body temperature decrease after giving aloe vera poultice was 0.64°C and 85% of it became normal. The results of the statistical test showed that aloe vera poultice was effective in lowering the body temperature of babies after DPT-HB vaccination (p 0.000). Community health centers were required to recommend to mothers the therapy of aloe vera as an alternative treatment for fever their babies might have after DPT-HB immunization.